2017
DOI: 10.1001/jamacardio.2017.3882
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect and Longitudinal Hemodynamic Assessment of Borderline Pulmonary Hypertension

Abstract: Borderline PH is common in patients undergoing RHC and is associated with significant comorbidities, progression to overt PH, and decreased survival. Small increases in mPAP, even at values currently considered normal, are independently associated with increased mortality. Prospective studies are warranted to determine whether early intervention or closer monitoring improves clinical outcomes in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 34 publications
6
96
0
5
Order By: Relevance
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this analysis are Valerio et al,10 Heresi et al,11 Kovacs et al,5 Suzuki et al,12 Maron et al,3 Takahashi et al,13 Douschan et al,4 Assad et al,2 Abramson et al,14 Kjaergaard et al,15 Shalaby et al,16 Lam et al,17 Damy et al,18 Cabrita et al,19 and Choudhary et al 20. CI indicates confidence interval; M‐H, Mantel‐Haenszel; RHC, right heart catheterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 20% of subjects without a TRV had a mPAP >35 mm Hg, which would have remained undetected had they not also been referred for RHC. Moreover, detecting even mild elevations in pulmonary pressure is important based on recent reports showing that “borderline” values of mean pulmonary pressure are reproducibly associated with increased adjusted mortality 14, 15. Additionally, the no‐TRV group may be earlier in the disease process relative to the TRV group and may in fact develop more readily measurable TRV Doppler signals over time.…”
Section: Discussionmentioning
confidence: 99%